Women's Dynamics in Local Economic Development Metro City Case Study: Justice Perspective - Rizal Bahrul Mustofa (Brajamusti Publication, 2025)
This article discusses the Contribution of Women to the Local Economy of Metro City. Economic development is the main foundation for creating overall community welfare. Women play a crucial role in the economic sector, particularly through their contributions to Micro, Small, and Medium Enterprises, which are the backbone of the local economy. However, women still face various challenges, including limited access to capital, minimal entrepreneurship training, low financial literacy, and the burden of household responsibilities. The research method used is qualitative with documentation techniques, collecting data from various written sources such as books, journals, reports, and other relevant documents. Content analysis techniques were applied to understand the challenges and contributions of women to the local economy of Metro City. The results show that women contribute to the MSME sector, particularly in the culinary sector, which supports job creation and economic growth. However, they still face structural and cultural barriers that affect business sustainability. Therefore, sustainable entrepreneurship and financial literacy training programs are needed to support women's empowerment. Recommendations for inclusive government policy support and strengthening the MSME ecosystem can help increase women's contribution to local economic development.